Injury surveillance in multi-sport events: the International Olympic Committee approach. Issue 6 (7th April 2008) - Junge, A; Engebretsen, L; Alonso, J M; Renström, P; Mountjoy, M; Aubry, M; Dvorak, J
Abstract : Background: The protection of athletes' health by preventing injuries is an important task for international sports federations. Standardised injury surveillance provides not only important epidemiological information, but also directions for injury prevention, and the opportunity for monitoring long-term changes in the frequency and circumstances of injury. Numerous studies have evaluated sports injuries during the season, but few have focused on injuries during major sport events such as World Championships, World Cups or the Olympic Games. Objectives: To provide an injury surveillance system for multi-sports tournaments, using the 2008 Olympic Games in Beijing as an example. Methods: A group of experienced researchers reviewed existing injury report systems and developed a scientific sound and concise injury surveillance system for large multi-sport events. Results: The injury report system for multi-sport events is based on an established system for team sports tournaments and has proved feasible for individual sports during the International Association of Athletics Federations World Championships in Athletics 2007. The most important principles and advantages of the system are comprehensive definition of injury, injury report by the physician responsible for the athlete, a single-page report of all injuries, and daily report irrespective of whether or not an injury occurred. Implementation of the injury surveillance system, all definitions, the report form, and the analysis of data are described in detail to enable other researchers to implement the injury surveillance system in any sports tournament. Conclusion: The injury surveillance system has been accepted by experienced team physicians and shown to be feasible for single-sport and multi-sport events. It can be modified depending on the specific objectives of a certain sport or research question; however, a standardised use of injury definition, report forms and methodology will ensure the comparability of results.